DETERMINATION OF OPTIMAL SOWING SCHEMES FOR PUMPKIN VARIETIES UNDER WATER-SAVING TECHNOLOGY - Alisher Juraboevich Shokirov; Maksad Muratovich Matyakubov (Modern American Journals, 2025)
When cultivating pumpkin varieties Spanish 73, Shirintoy, Elegant, Konfetka, Japanese, and Vitamin under a resource-saving, water-conservation technology using different planting schemes—double-row (360+90)/2×80 cm; (270+90)/2×90 cm; and single-row 180×90 cm and 180×60 cm—it was found that, for all varieties, the earliest fruit maturation occurred in the variant with the 180×90 cm sowing scheme, where fruits ripened 3–12 days earlier compared with the control and other variants. Marketable yield was also higher than in the control and other treatments: for Spanish 73 by 17.1–65.5%, Elegant by 22.3–91.2%, Konfetka by 15.2–29.0%, Shirintoy by 11.8–75.9%, Japanese by 12.3–46.3%, and Vitamin by 12.2–50.0%.
Keywords: Saline soil, resource-saving, water-saving, control, replication, variety, treatment, scheme, productivity, yield, marketable yield.